Simplification
- 3√(333)3 + (333)3 + (334)3 − 3 × 333 × 333 × 334 is equal to
-
View Hint View Answer Discuss in Forum
We know that
a3 + b3 + c3 – 3abc
= (a+b+c ) (a2 + b2 + c2 – ab – bc – ca)= 1 (a + b + c)[(a – b)2 + (b – c)2 + (c – a)2] 2
∴ 3√(333)3 + (333)3 + (334)3 − 3 × 333 × 333 × 334
= 3√(1/2)(333 + 333 + 334) [(333 − 333)2 + (333 − 334)2 + (334 − 333)2]
= 3√(1/2) × 1000 × 2
= 3√1000
= 3√10 × 10 × 10
= 10Correct Option: C
We know that
a3 + b3 + c3 – 3abc
= (a+b+c ) (a2 + b2 + c2 – ab – bc – ca)= 1 (a + b + c)[(a – b)2 + (b – c)2 + (c – a)2] 2
∴ 3√(333)3 + (333)3 + (334)3 − 3 × 333 × 333 × 334
= 3√(1/2)(333 + 333 + 334) [(333 − 333)2 + (333 − 334)2 + (334 − 333)2]
= 3√(1/2) × 1000 × 2
= 3√1000
= 3√10 × 10 × 10
= 10
-
The value of 4 − √0.04 is close to 4 + √0.4
-
View Hint View Answer Discuss in Forum
Expression = 4 − √0.04 4 + √0.4 = 4 − 0.02 4 + 0.6 = 3.8 = 38 = 19 4.6 46 23
≈ 0.83 ≈ 0.8Correct Option: A
Expression = 4 − √0.04 4 + √0.4 = 4 − 0.02 4 + 0.6 = 3.8 = 38 = 19 4.6 46 23
≈ 0.83 ≈ 0.8
-
√ 0.25 × √ 0.09 is equal to : 0.0009 0.36
-
View Hint View Answer Discuss in Forum
= √ (0.25 × 0.09) 0.0009 × 0.36 = √ 25 × 9 × 1000000 9 × 36 × 10000 = 5 × 10 = 25 = 8 1 6 3 3 Correct Option: D
= √ (0.25 × 0.09) 0.0009 × 0.36 = √ 25 × 9 × 1000000 9 × 36 × 10000 = 5 × 10 = 25 = 8 1 6 3 3
-
The simplified value of 4 of 5 × 6 + 15 – 10 is 15 8
-
View Hint View Answer Discuss in Forum
Expression = 4 of 5 × 6 + 15 – 10 15 8
= 1 + 15 – 10 = 16 – 10 = 6Correct Option: A
Expression = 4 of 5 × 6 + 15 – 10 15 8
= 1 + 15 – 10 = 16 – 10 = 6
-
View Hint View Answer Discuss in Forum
= 79 14 5 + 9 14 = 79 14 5 + 70 + 9 14 = 79 × 14 = 1 14 79 Correct Option: A
= 79 14 5 + 9 14 = 79 14 5 + 70 + 9 14 = 79 × 14 = 1 14 79